SBRT: An Opportunity to Improve Quality of Life for Oligometastatic Prostate Cancer - Azzam, Gregory; Lanciano, Rachelle; Arrigo, Steve; Lamond, John; Ding, William; Yang, Jun; Hanlon, Alexandra; Good, Michael; Brady, Luther (Frontiers in Oncology, 2015)
Objective Oligometastatic prostate cancer is a limited metastatic disease state in which potential long-term control is still possible with the use of targeted therapies such as surgery or stereotactic body radiation therapy (SBRT). SBRT may as well potentially prolong the time before the initiation of androgen deprivation therapy (ADT) and docetaxel chemotherapy for oligometastatic prostate cancer. The goal of this study is to outline prognostic factors associated with improved outcome with SBRT for metastatic prostate cancer and to quantify the effect of prior systemic treatments such as ADT and docetaxel on survival after SBRT. Methods Twenty-four prostate cancer patients were treated with SBRT at the Philadelphia CyberKnife Center between August 2007 and April 2014. Retrospective data collection and analysis were performed for these patients on this Institutional Review Board approved study. Kaplan–Meier methodology was utilized to estimate and visually assess overall survival (OS) at the patient level, with comparisons accomplished using the log-rank test. Unadjusted hazard ratios were estimated using Cox proportional hazards regression modeling. Results An improved median survival was noted for patients with oligometastatic disease defined as ≤4 lesions with median survival of >3 years compared with 11 months for polymetastases (p = 0.02). The use of docetaxel at some time in follow-up either before or after SBRT was associated with decreased survival with median survival of 9 months vs. >3 years (p = 0.01). Conclusion Prognosis was better for men with recurrent prostate cancer treated with SBRT if they had ≤4 metastases (oligometastases) or if docetaxel was not necessary for salvage treatment. The prolonged median OS for men with oligometastases in this population of heavily pretreated prostate cancer patients following SBRT may allow for improved quality of life because of a delay of more toxic salvage therapies.